Characteristics and genetic mechanisms of offshore natural gas in the Nanpu Sag, Bohai Bay Basin, eastern China. (April 2016) - Chen, Xiangfei; Li, Sumei; Dong, Yuexia; Pang, Xiongqi; Wang, Zhengjun; Ren, Miaosong; Zhang, Hongchen
Highlights: Oil-type, coal-type and mixed-source gas are recognized in Nanpu offshore area. Shallow gas is primarily oil-type sourced from Ed3 –Es1 source rocks with I–II1 kerogen. Deep gas is primarily coal-type derived from Es2+3 source rocks with II2 –III kerogen. Primary cracking of kerogen is responsible for most discovered gases. There is considerable deep gas potential in the Nanpu Sag and the similar basins. Abstract: Recently, great breakthroughs in natural gas exploration have been achieved in the Nanpu Sag, Bohai Bay Basin, eastern China; however, the genetic type and formation mechanisms of the gas are still unclear, impeding further exploration. Chemical and isotopic compositions were investigated to determine the origins for the gas. Three groupings of the natural gases are recognized: oil-type gas, coal-type gas, and mixed-source gas. The oil-type gases are relatively depleted in 13 C (δ 13 C1  < −43‰); δ 13 C2  < −29‰ and low wetness (0.60–0.89). The coal-type gases are enriched in 13 C (δ 13 C1  > −40‰; δ 13 C2  > −28‰) with higher wetness (0.80–0.95). The third grouping of gases exhibits intermediate molecular and isotopic values. Most of the gases in the shallow layers of the No. 1 and 4 structural belts have δ 13 C values similar to those of underlying gases and display evidence for microbial alteration. Primary cracking of kerogen is responsible for the generation of most of this gas. Pyrolysis of the source rocks combined with maturity estimations revealed that the relatively shallow oil-type gas was derived primarily from Oligocene and Eocene (Ed3 –Es1 ) source rocks bearing Type I–II1 kerogen, whereas the coal-type gas was generated from the Eocene (Es2+3 ) source rocks containing II2 –III kerogen. We concluded that the kerogen type and maturity of the source rocks and the activity of source-connecting faults primarily controlled the distribution of the different gases. We suggest that there is significant deep gas potential in the Nanpu Sag, perhaps even over the whole Bohai Bay Basin, that would be prospective for further deep gas exploration in the area.